Inclusive attitudes: typically developing students and students with disabilities in UAE classrooms - Dukmak, Samir; Abo Hamza, Eid G.; Alkhatib, Razan; Daghustani, Wid; Bedewy, Dalia (Frontiers in Education, 2024)
Research on students' attitudes towards inclusive education in the UAE is limited, with a focus on qualitative investigations of parents and teachers. This study addresses this gap by developing the Students' Attitude Scale to measure attitudes towards inclusive education. We examined the impact of age, grade level, nationality, educational placement, and gender on inclusive education using a sample of 355 students from diverse UAE districts. Findings reveal that female students scored significantly higher than males on the scale. While Emirati nationals showed higher scores, the difference was not statistically significant. Notably, students in the "All Day in Regular Classroom with the Necessary Support" placement had higher scores. Grade level and UAE district did not significantly influence attitudes. Our study emphasizes the positive influence of gender and increased interaction with students with disabilities on fostering favorable attitudes towards inclusive education. These insights can inform efforts to enhance inclusive practices in the UAE.